Phytochemical profiling and evaluation of antimicrobial activities of common culinary spices: Syzygium aromaticum (clove) and Piper nigrum (black pepper) - Zhao, Kexin; Wonta, Kou B.; Xia, Jinquan; Zhong, Fuhua; Sharma, Vipasha (Frontiers in Nutrition, 2024)
The increasing resistance of microbial pathogens to conventional antibiotics necessitates the exploration of alternative antimicrobial agents. This study aims to evaluate the antimicrobial potential and phytochemical properties of Syzygium aromaticum (clove) and Piper nigrum (black pepper) extracts, both of which are known for their historical use in traditional medicine and culinary applications. Methods:Hydroalcoholic and aqueous extracts of clove and black pepper were prepared. The antimicrobial activity of these extracts was assessed using the disk diffusion method against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans, and Aspergillus niger. Minimum inhibitory concentration (MIC) was determined using the broth dilution method. Qualitative phytochemical screening identified the presence of key bioactive compounds, while quantitative analysis measured total phenolic and flavonoid contents. LC-HRMS/MS analysis of ethanolic extracts was performed. Results: Both spices extracts exhibited significant antimicrobial activity, with inhibition zones ranging from 14 to 18 mm. clove showed superior antimicrobial efficacy compared to black paper, particularly against fungi. MIC values ranged between 3 mg/mL and 6 mg/mL for both spices. Phytochemical analysis revealed higher total phenolic and flavonoid contents in clove, with hydroalcoholic extracts showing greater concentrations than aqueous extracts. HPLC quantified higher eugenol content in clove extracts and higher piperine content in black pepper extracts. The differences in bioactive compound content were statistically significant (p< 0.05). Conclusion: The study confirms that both spices possess significant antimicrobial properties, attributable to their rich phytochemical composition, particularly phenolics and flavonoids. clove exhibited slightly superior antimicrobial activity compared to black paper. These findings support the potential use of these spices as complementary antimicrobial agents. Further research should investigate their synergistic effects with conventional antibiotics and explore their applications in food preservation and alternative medicine.